The Winning Cars of the Indianapolis 500 - Reinhardt, James Craig (Book collections on Project MUSE., 2019)
Featuring nearly 200 images of the automobiles and individuals who make the Indianapolis 500 renowned, this book showcases the top drivers and how racing has changed through two world wars, the Great Depression, and unforgettable accidents.